A universal method for constructing high efficiency organic solar cells with stacked structures. Issue 4 (4th March 2021) - Wei, Yanan; Yu, Jianwei; Qin, Linqing; Chen, Hao; Wu, Xiaoxi; Wei, Zhixiang; Zhang, Xin; Xiao, Zuo; Ding, Liming; Gao, Feng; Huang, Hui
Abstract : Quantitative relationship between the protective factor ( δ ) and PCE of stacked structures of OSC with a record PCE of 17.52% is proposed to understand the mechanism and provide a guideline for solvent choices of eco-friendly solvent protection method. Abstract : The construction of organic solar cells with stacked structures by the sequential deposition (SD) of donor and acceptor films has great potential in industrial production, as it demonstrates little dependence on the ratio of donor and acceptor materials, solvents, and additives. Herein, we present an eco-friendly solvent protection (ESP) method for the fabrication of high-performance OSCs with stacked structures. Several non-aromatic and non-halogenated solvents are employed as protective agents to build SD devices with a configuration of indium tin oxide (ITO)/poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS Clevios P VP Al 4083)/donor/protective solvent/acceptor/perylene diimide functionalized with amino N -oxide (PDINO)/Al, which shows that n -octane is the optimal choice for SD devices. Nine different SD systems including the fullerene and nonfullerene ones present comparable photovoltaic performance to their BC counterparts, which proves the universality of this ESP method. Significantly, the device of ITO/PEDOT:PSS/D18/N3/PDINO/Al with n -octane as the protective solvent achieves a maximum PCE of 17.52%, which is the record efficiency of SD devices. Furthermore, a protective factor ( δ ) is proposed to demonstrate the quantitative relationship between δ and PCE after experimental and theoretical investigation, which presents an idea to understand the mechanism and provides a guideline for solvent choices.